Influence of 8-weeks of supervised static stretching or resistance training of pectoral major muscles on maximal strength, muscle thickness and range of motion - Tim Wohlann; Konstantin Warneke; Vincent Kalder; David G. Behm; Tobias Schmidt; Stephan Schiemann (European Journal of Applied Physiology, 2024)
Objectives Current research suggests static stretch-induced maximal strength increases and muscle hypertrophy with potential to substitute resistance-training routines. However, most studies investigated the plantar flexors. This study explored the effects of a static stretching program on maximal strength, hypertrophy and flexibility of the pectoralis major and compared the effects with those of traditional resistance training. Methods Eighty-one (81) active participants were allocated to either a static stretching, strength-training or control group. Pectoralis stretching was applied 15 min/day, 4 days per week for 8 weeks, while resistance training trained 3 days per week, 5 × 12 repetitions. Results There was an increase in all parameters (strength: p < 0.001, ƞ 2 = 0.313, muscle thickness: p < 0.001, ƞ 2 = 0.157–0.264, flexibility: p < 0.001, ƞ 2 = 0.316) and a time*group interaction (strength: p = 0.001, ƞ 2 = 0.154, muscle thickness: p = 0.008–0.001, ƞ 2 = 0.117–0.173, flexibility: p < 0.001, ƞ 2 = 0.267). Post-hoc testing showed no difference between both intervention groups regarding maximal strength and muscle thickness ( p = 0.905–0.983, d = 0.036–0.087), while flexibility increased in the stretching group ( p = 0.001, d = 0.789). Conclusion Stretching showed increases in maximal strength and hypertrophy, which were comparable with commonly used resistance training. Based on current literature, the influence of mechanical tension as the underlying mechanism is discussed. Furthermore, as equipment and comparatively long stretching durations are requested to induce meaningful strength increases in recreationally active participants, practical application seems limited to special circumstances.

Comparison of the effects of long-lasting static stretching and hypertrophy training on maximal strength, muscle thickness and flexibility in the plantar flexors - Konstantin Warneke; Klaus Wirth; Michael Keiner; Lars H. Lohmann; Martin Hillebrecht; Anna Brinkmann; Tim Wohlann; Stephan Schiemann (European Journal of Applied Physiology, 2023)
Maximal strength measured via maximal voluntary contraction is known as a key factor in competitive sports performance as well as injury risk reduction and rehabilitation. Maximal strength and hypertrophy are commonly trained by performing resistance training programs. However, literature shows that long-term, long-lasting static stretching interventions can also produce significant improvements in maximal voluntary contraction. The aim of this study is to compare increases in maximal voluntary contraction, muscle thickness and flexibility after 6 weeks of stretch training and conventional hypertrophy training. Sixty-nine (69) active participants ( f = 30, m = 39; age 27.4 ± 4.4 years, height 175.8 ± 2.1 cm, and weight 79.5 ± 5.9 kg) were divided into three groups: IG1 stretched the plantar flexors continuously for one hour per day, IG2 performed hypertrophy training for the plantar flexors (5 × 10–12 reps, three days per week), while CG did not undergo any intervention. Maximal voluntary contraction, muscle thickness, pennation angle and flexibility were the dependent variables. The results of a series of two-way ANOVAs show significant interaction effects ( p < 0.05) for maximal voluntary contraction ( ƞ 2 = 0.143–0.32, p < 0.006), muscle thickness ( ƞ 2 = 0.11–0.14, p < 0.021), pennation angle ( ƞ 2 = 0.002–0.08, p = 0.077–0.625) and flexibility ( ƞ 2 = 0.089–0.21, p < 0.046) for both the stretch and hypertrophy training group without significant differences ( p = 0.37–0.99, d = 0.03–0.4) between both intervention groups. Thus, it can be hypothesized that mechanical tension plays a crucial role in improving maximal voluntary contraction and muscle thickness irrespective whether long-lasting stretching or hypertrophy training is used. Results show that for the calf muscle, the use of long-lasting stretching interventions can be deemed an alternative to conventional resistance training if the aim is to increase maximal voluntary contraction, muscle thickness and flexibility. However, the practical application seems to be strongly limited as a weekly stretching duration of up to 7 h a week is opposed by 3 × 15 min of common resistance training.

Acute effects of long-lasting stretching and strength training on maximal strength and flexibility in the calf muscle - Konstantin Warneke; Tim Wohlann; Lars H. Lohmann; Klaus Wirth; Stephan Schiemann (German Journal of Exercise and Sport Research, 2023)
The so-called “stretch-induced force deficit” is known from a large amount of research. There are many theories trying to explain the stretch-induced force deficit and increases in the range of motion (ROM) which all offer a stretch training-specific explanation. However, when performing a commonly used strength training session, a reduced maximum strength (MSt) capacity can be assumed as well. Based on this, the aim of the study is to investigate the tension-induced force deficit due to a suprathreshold strength or stretching training stimulus. Therefore, 71 participants (age: 24.1 ± 4.2 years, height: 176.3 ± 5.7 cm, weight: 74.1 ± 7.5 kg) were divided into three groups: static stretching group (SST), strength training group (STR), and control group (CG). To investigate possible mechanical tension-induced force deficits, SST performed a long-lasting static stretching intervention for 1 h using an orthosis, while STR executed a common strength training intervention (5 × 12 repetition) for the plantar flexors. The results show a significant reduction of measured MSt as well as increased ROM for both SST and STR following the interventions. Consequently, we found similar acute effects of stretching and strength training regarding MSt and flexibility. We conclude that the decreased MSt capacities can possibly be attributed to mechanical tension-induced damage of the muscle that is not linked to a specific training method. The improvements in flexibility found in both intervention groups might be attributed to warm up effects when inducing high mechanical tension to large ankle joint angles.